PENGELOLAAN PEMBELAJARAN KONTEKSTUAL PENDIDIKAN AGAMA ISLAM - Nafia, Akhmad Ilman (Graduate Program Magister Manajemen Pendidikan, 2016)
The management of contextual learning in Islamic Education consist of planning which is done by technical and non technical analysis, and planning of the learning scenarios related to the material and the objective conditions that is experienced by the students. The implementation of contextual learning of Islamic education was the inquiry, questioning, learning community, modeling, reflecting, and contextual learning evaluation to the behavioral change, the school community as the basic of valuation.Â Keywords: Management, Contextual Learning, Islamic EducationÂ